2001
DOI: 10.4319/lo.2001.46.3.0689
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir circulations disturb the low‐oxygen refuge of phantom midge larvae

Abstract: The previously unknown effects of wind‐induced Langmuir circulations on the distribution of phantom midge larvae (Chaoborus flavicans) were studied by echosounding. The study was carried out in the eutrophic Lake Hiidenvesi, where chaoborids use a metalimnetic oxygen minimum as a daytime refuge against fish predation. At a wind velocity of 8—9 m s−1, the upwelling water circulations snatched clouds of chaoborids from the metalimnion (12‐15 m depth) to the more oxygenated epilimnion. The average density of C. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Analysis of fish in the presence of Chaoborus has been a long unsolved problem making it difficult to perform fish stock assessment (Eckmann 1998;Malinen et al 2001;. We have demonstrated that using a 38 kHz frequency removes echoes from Chaoborus to such an extent that an unbiased fish assessment can be obtained.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Analysis of fish in the presence of Chaoborus has been a long unsolved problem making it difficult to perform fish stock assessment (Eckmann 1998;Malinen et al 2001;. We have demonstrated that using a 38 kHz frequency removes echoes from Chaoborus to such an extent that an unbiased fish assessment can be obtained.…”
Section: Discussionmentioning
confidence: 91%
“…The larva possesses two pairs of air-sacs and is a strong acoustic scatterer at the echosounder frequencies traditionally used in freshwater (Northcote 1964;Eckmann 1998;Wagner-Döbler and Jacobs 1998;Malinen et al 2001Malinen et al , 2005Knudsen et al 2006). When they co-occur with fish, Chaoborus display a diel vertical migration, where they are found in the sediments or in the hypolimnion during the day and ascend into the epilimnion to feed in the evening (Malueg and Halser 1966;Nilsen 1974;Voss and Mumm 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often acting as the most common planktivore besides fish (Wissel et al 2003), they contribute to high biomasses in eutrophic lakes (Malinen et al 2001) and can greatly affect zooplankton community structure (Moore 1988). Certain populations of Chaoborus often exhibit diel vertical migration (DVM), a behavior characterized by staying in deeper waters during daytime hours and ascending nocturnally to feed (Dodson 1990).…”
mentioning
confidence: 99%